Tomorrow’s agri-food system: The connections between trade, food security, and nutrition for a sustainable diet - Laborde Debucquet, David; Piñeiro, Valeria; Swinnen, Johan (Routledge, 2023)
The nexus between trade, climate change, and nutrition is important in the conversation of sustainable diets. Understanding these interactions, as well as highlighting their synergies and limiting the trade-offs between them, will give some insights on how food systems can be transformed to provide affordable healthy diets to all in a sustainable way. In this context, policy incentives could play an important role in transforming existing systems. Trade in agricultural products is an important factor both in improving global food security and its impact on global dietary trends. Trade policies should accompany each country’s sustainable diet objectives by working within existing trade rules to create better outcomes for nutrition.